Localization of RNA Pol II CTD (S5) and Transcriptome Analysis of Testis in Diploid and Tetraploid Hybrids of Red Crucian Carp (♀) × Common Carp (♂) - Zhou, Yi; Zhu, La; Sun, Yu; Zhang, Hui; Wang, Jiaojiao; Qin, Weilin; He, Wangchao; Zhou, Luojing; Li, Qi; Zhao, Rurong; Luo, Kaikun; Tang, Chenchen; et al. (Frontiers in Genetics, 2021)
Polyploidization of fishes occurs in nature but appearance of these species is occasional and gradual process which is hard to trace the changes in phenotypes, genotypes and regulations of gene expression. The allotetraploid hybrids (4nAT) of red crucian carp (RCC) (♀) × common carp (CC) (♂) generated from interspecies crossing provide a great opportunity for investigating the initial changes after allopolyploidization. In the present study, we focused on the changes of active sites of testicular transcriptome in the allotetraploid from genome sight by localization of RNA Pol II CTD (S5) using immunofluorescence and RNA-seqs data via bioinformatic analysis. The results showed that there was no significant difference of signal counts of the RNA Pol II CTD (S5) comparing among the different type of fishes in the same stages, including RCC, CC, 2nF1 and 4nAT, which mean that the number of transcriptional active sites on germ cell chromosomes was not changed by the increaseof chromosome number. Similarly, the RNA-seq analysis indicated that whether in the levels of chromosomes and 10kb regions in genome, no significant changes of the high active sites in RCC, 2nF1 and 4nAT. These clues suggested that at the beginning of allotetraploid, the active transcriptome site of 4nAT in testis were conserved in the regions in genome compared to RCC and 2nF1. In conclusion, 4nAT shared similar gene expression model in the regions of genome to RCC and 2nF1 with significant different expression levels.